The effects of carbohydrate ingestion on the badminton serve after fatiguing exercise - Bottoms, L.; Sinclair, J.; Taylor, K.; Polman, R.; Fewtrell, D. (Journal of Sports Sciences, 2012)
The badminton serve requires great skill and may be affected by fatigue. The aim of the present study was to determine whether carbohydrate ingestion affects badminton performance. Nine male badminton players (age 25 ± 7 years, mass 80.6 ± 8.0 kg) attended the laboratory on three occasions. The first visit involved an incremental exercise test to exhaustion to determine peak heart rate. Participants were given 1 L of a carbohydrate-electrolyte drink or a matched placebo during the experimental trials. The accuracy of 10 long and 10 short serves was determined before and after exercise. The fatiguing exercise was 33 min in duration (83 ± 10% and 84 ± 8% peak heart rate for the placebo and carbohydrate trial respectively). Capillary blood samples (20 µL) were taken before and after exercise for determination of blood glucose and lactate. There was deterioration in long serve accuracy with fatigue (P = 0.002), which carbohydrate ingestion had a tendency to prevent (P = 0.077). There was no effect of fatigue (P = 0.402) or carbohydrate ingestion (P = 0.109) on short serve accuracy. There was no difference in blood glucose concentration between trials (P = 0.851). Blood lactate concentration was higher during the placebo trial (P = 0.016). These results suggest that only the long serve is influenced by fatigue and carbohydrate had a tendency to prevent the deterioration in performance.